Engineering high voltage aqueous aluminum-ion batteries - Hu, Erhai (2024)
The energy transition to renewables necessitates innovative storage solutions beyond the capacities of lithium-ion batteries. Aluminum-ion batteries (AIBs), particularly their aqueous variants (AAIBs), have emerged as potential successors due to their abundant resources, electrochemical advantages, and eco-friendliness. However, they grapple with achieving their theoretical voltage potential, often yielding less than expected. This perspective article provides a comprehensive examination of the voltage challenges faced by AAIBs, attributing gaps to factors such as the aluminum reduction potential, hydrogen evolution reaction, and aluminum's inherent passivation. Through a critical exploration of methodologies, strategies, such as underpotential deposition, alloying, interface enhancements, tailored electrolyte compositions, and advanced cathode design, are proposed. This piece seeks to guide researchers in harnessing the full potential of AAIBs in the global energy storage landscape.